Efecto de diez Extractos Vegetales sobre Fusarlum oxysporum aislado de Cebolla China (Allium fistolosum L.) bajo condiciones de laboratorio e invernadero en San Martín. - Díaz Chuquizuta, Percy (2006)
The objective was to evaluate the etfect of the dOses of vegetable extracts in the control of F. oxysporum in laboratory and hothouse. For the test in Laboratory was gathered sampleS of Chinese onion (Allium listolosum) sick persons. The extracts got ready weighing 100 g of each plant. The leaves were crushed and the sedes were milled I enlarge distilled water, resting for 24 h, adding the respective doses to the means Of Cultivation PDA. For this test the Design was used Totally at random (DCA) With factorial arrangement 10 (you plant) x 4 (dose: o ml, 1 ml, 2 ml and 4 ml) and the duncan test (at the 0,05). In this test the extracts of /. purpurea 1 ml, of M. pudica 1 ml, or Rosa sp 4ml, A indica of 1 ml, R. communis 4ml, E. fosbergil 1 ml and s. torvum 1ml Obtained effect on the colony size with averages of 7,225; 7,225; 7,07; 7,05; 6,96; 6,752 and 6,68 cm respectively with regard to the witness (9,2 cm), being usad for the hothouse phase where the preparation of extracts was the same one that in laboratory. For this test a design was used totally at random (DCA) with 8 treatments and 5 observations, carrying out the test from Duncan to the 0,05, obtaining results the emergency with the extracts of S. torvum (10ml) with 71,21 % and M. pudica (10ml) with 71,524%, being smaller with regard to the other treatments; for the incidence the best extracts ware R. communis (40ml/l) with 72%, A. indica (10ml/l) with 64,15% and l. purpurea (10ml/l) with 61,15%. Obtaining percentages of efficiency in the control of 14,98; 24,25 and 27,8 respectively; in the % of seventy the extracts of A. indica (10ml/l) and l. purpurea (10ml/I), they slowed the advance of the illness until the grade 3 at the end of the evaluation.